Cobalt-catalyzed coupling reactions of 2-halobenzamides with alkynes: investigation of ligand-controlled dual pathways. Issue 22 (5th October 2021) - Thorat, Vijaykumar H.; Aman, Hasil; Tsai, Yu-Lin; Pallikonda, Gangaram; Chuang, Gary Jing; Hsieh, Jen-Chieh
Abstract : The Co-catalyzed reactions of 2-halobenzamides and alkynes to form quinolinones or 2-vinyl benzamides are described here. These two reactions can be controlled merely by ligands. Abstract : The Co-catalyzed reactions of 2-halobenzamides and alkynes to form isoquinolones or 2-vinyl benzamides are described here. The formation of the two selective products can be fully controlled by adopted ligands. A study of the mechanism demonstrated that these two reactions proceed through different pathways. The radical process and the two-electron transfer activation of the C–X bond are respectively proposed for these two reactions.